Effectiveness of Behavioral Counseling with Modeling Techniques to Improve Affiliate Self for students of class VII H Middle School 3 Singaraja - Seniasih, Linda; Suranata, kadek (Bisma The Journal of Counseling, 2018)
The purpose of this study is to determine the effectiveness of behavioral counseling with modeling techniques to increase affiliation in class VII H students of SMP Negeri 3 Singaraja. Research This experiment used a pretest-posttest control group design. The research population is students of class VII of SMP Negeri 3 Singaraja Buleleng Bali. Through random sampling technique, a sample of 69 students (male 30, female 39. average age 14 years) was obtained. 35 students were placed in the Experiment group who received behavioral counseling with modeling techniques and 34 students in the control group without treatment. Research research data is collected with affiliate inventories. The data of this study were analyzed with a differential t-test using the JASP0.10.0.0 for Windows program and continued in Cohen to calculate effectiveness. The results of the analysis showed 1) a value of 0,01, significant at 0,01> 0.05 2) The effect size of 3,49 was categorized as high. This means that there is a significant difference in the value of students who are given treatment behavioral counseling modeling techniques. Students given treatment are higher in affiliation than students without treatment. Become behavioral counseling with effective modeling techniques to increase affiliation.